Mulher chefe de família, na cidade de Aracaju:dominação e poder - Chagas, Sylvia Oliveira (2010)
The research was focada in the feminine head of family, the City of Aracaju and its impacts in the nuclear familiar nucleus. Considering that, the papers of the men are in general, not valued and rewarded that the papers of the women in almost all the cultures. The women generally load the responsibility to take care of of the children and the domestic work, while the men traditionally are born with the responsibility to support the family. However, we find changes in this mainly north-eastern scene and, where through quantitative research, already one evidenced that they are majority as family support, therefore, we observe the construction of social identities of the women family heads and uncurling of the adaptativos aspects, the existing mechanism between domination and power, in the familiar nucleus. The impacts in the family if had change in the social relation for them to be family heads. One is about qualitative research that has left of the construction of a theoretical landmark, analyzing given of bibliographical sources and from interviews with women family heads, power to observe the forms of joints in the nuclear families, as they deal with the power to decide power, the financial power, the fragility, the domination and the influences of the traditional models. Analyzing the familiar relations between the woman, the children and the spouse, searching the excellent questions for the briefing of the thematic one, demystifying the dichotomy between the mother/wife and woman head of family in the residential environment